A Social Network Approach to the Dual Aspect of Moral Competence - Salej Higgins, Silvio; Vega Sanabria, Guillermo; Unger Raphael Bataglia, Patrícia; Fontenele Gonçalves, Erick; Ferreira da Silva Carmo, Lavínia (ETHICS IN PROGRESS, 2023)
This work presents evidence supporting the relationship between the dual aspect of moral competence (emotion and cognition) and social networks in school settings. We conducted empirical research with 160 students from various disciplines of the social sciences and different cohorts in two Brazilian public universities. Firstly, the participants responded to Georg Lind’s Moral Competence Test (MCT-xt). Following this, a sociometric generator regarding relationships of friendship and collaboration in social networks was applied, and several Exponential Random Graphs Models (ERGMs), with the MCT-xt score as an exogenous effect and predictor of these relationships, were utilized. We also used a Crisp-Set Qualitative Comparative Analysis in order to determine if the cohorts, where the average MCT-xt was associated with the interactional structure, obeyed the same causal configuration. There exist two conditional configurations: (1) a sufficient score of MCT-xt in a social network with homogeneous status encourages a proactive search of collaboration; (2) an insufficient score of MCT-xt in a social network with homogeneous status encourages a collaborative exchange based on the popularity of some individuals. This work reveals how to interpret, at the grouping level, the results of MCT-xt.